2007
DOI: 10.1016/j.febslet.2007.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Resistin down‐regulates insulin receptor expression, and modulates cell viability in rodent pancreatic beta‐cells

Abstract: The adipokine resistin is known to induce insulin resistance in rodent tissues. Increases in adipose tissue mass are known to have a negative effect on pancreatic beta-cell function, although the mechanisms are poorly understood. This study investigated the effects of resistin on insulin secretion, insulin receptor expression and cell viability in pancreatic beta-cells. BTC-6 or BRIN-BD11 cells were treated for 24 h with resistin, and insulin receptor expression, insulin secretion and cell viability were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…14 This observation may confirm that resistin contributes to insulin resistance in islets. In BRIN-BD11 b cell line resistin failed to affect insulin secretion at supraphysiologically high glucose (22 mM).…”
supporting
confidence: 72%
“…14 This observation may confirm that resistin contributes to insulin resistance in islets. In BRIN-BD11 b cell line resistin failed to affect insulin secretion at supraphysiologically high glucose (22 mM).…”
supporting
confidence: 72%
“…This mechanism is consistent with gene targeting studies in mice that demonstrated proximal insulin signalling to be required to maintain adequate beta cell mass and function (Cantley et al 2007;Kulkarni et al 1999). Another study showed that 24-h resistin treatment of b-TC6 beta cells decreased insulin receptor mRNA levels, whereas treatment of BRIN-BD11 beta cells did not affect insulin secretion (Brown et al 2007). In studies of fixed human pancreata, resistin was shown to be expressed in human beta cells, but not alpha cells, and its expression increased with T2D (AlSalam et al 2011).…”
Section: Resistinsupporting
confidence: 50%
“…However, Brown et al(2007) reported that incubation with 40 ng/ml resistin significantly decreased insulin receptor mRNA and protein expression, but did not affect insulin secretion in mice. Liu et al(2006) found that rat resistin concentrates in the cytoplasm around cell nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of resistin in inducing insulin resistance remains poorly understood. It was reported that resistin down-regulated mRNA and protein expression of insulin receptor in rodent pancreatic beta-cells, but did not affect insulin secretion (Brown et al, 2007).…”
Section: Introductionmentioning
confidence: 99%